Composição mineral da carcaça e dos cortes da carcaça de ovinos jovens e adultos - Pinheiro, Rafael Silvio Bonilha [UNESP]; da Silva Sobrinho, Americo Garcia [UNESP]; de Andrade, Ernani Nery [UNESP] (My University, 2011)
Aiming to evaluate the mineral composition (iron, calcium and sodium) of the carcass and carcass cuts of meat from different ovine categories, 18 1/2 Ile de France 1/2 Polwarth sheeps (6 uncastrated lambs, 6 discarded ewes and 6 discarded wethers) were used. Animals were in grazing system based on Tifton - 85 pastures and were supplemented with concentrate. Lambs were slaughtered at 32 kg of live weight, at around 5 months of age. Ewes and wethers were slaughtered with 55 kg and 60 months of age. The iron values were differents between categories for those valued cuts muscles, with higher average to legs muscles from adults ovine of 3.86 mg/100g with regard to lambs of 1.91 mg/100g, respectively. The iron values of the muscles from half carcass didn't differ for that animal category, with 3.38 mg/100g average. The calcium values in muscles from half carcass and leg cut were higher to wethers (9.84 e 7.35 mg/100g), intermediaries to ewes (6.28 e 6.54 mg/100g) and smallers values to lambs (5.30 e 4.22 mg/100g). There wasn't differences for sodium values to valued categories and muscles, with values around 56.75 mg/100g. In conclusion, the sodium values are similar between animals categories and from differents carcass muscles and that the iron and calcium values present differences.
Mineral composition of the carcass and carcass cuts from young and adult sheeps
Keywords: Animal categories; Ewes; Minerals; Muscles